Correlation Between Spirituality Levels and Anxiety Among First-Year Students in Health Science Programs - Elvina, Rodiana; Fitriani, Dwi Rahmah; Astiningsih, Ni Wayan Wiwin (Genius Journal, 2025)
Introduction: Students have various academic demands that must be completed, especially often students must complete within a specified period of time. Anxiety can occur because of many things that need to be solved immediately caused by stressors. The purpose of this study is to determine the relationship between spiritual level and anxiety in new students in the health study program of the University of Muhammadiyah East Kalimantan. Objective: The purpose of this study is to determine the relationship between spiritual level and anxiety in new students in the health study program of the University of Muhammadiyah East Kalimantan. Research Method: This study was quantitative with a cross-sectional design, sampling technique using random sampling technique and a research sample size of 271 respondents. The research instruments used the Daily Spiritual Experience Scale (DSES) and Depression Anxiety and Stress Scale (DASS-21) questionnaires, while the statistical test used the Rank Spearman test. Results: The study showed that most of the new students were in the category of high spiritual level, which was 160 respondents (59.0%), while the level of anxiety of students was mostly in the normal category, which was 123 respondents (45.4%). The results of the statistical test showed a correlation coefficient value of -0.429 and a p-value of 0.000 < 0,05. Conclusion: So it means that there is a relationship between spiritual level and anxiety in new students in the health study program of the University of Muhammadiyah East Kalimantan. With the strength of moderate correlation and the direction of negative relationships, which means that the higher the level of spirituality, the lower the anxiety experienced by students.